ANALISIS PEMBELAJARAN IPAS DENGAN PENERAPAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA - Rahmawati, Anna; Daimul Hasanah; Heri Maria Zulfiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by educational problems that occur in Indonesia. Indonesia has been experiencing a learning crisis for quite a long time, and this situation is getting worse due to the spread of the Covid-19 pandemic. Indonesia is implementing a new curriculum that presents learning approaches that further explore students' potential and makes students the center of learning activities, and we know this curriculum as the Merdeka Curriculum. In the Independent Curriculum, there are several learning approaches that are often applied in the implementation of learning. These approaches are systematic in nature and can help the learning process. One learning approach that is expected to help overcome these educational problems is by implementing differentiated learning. Differentiated learning is an effective approach that can be used to deal with the diversity of students and ensure that it can meet the learning needs of diverse students, help students to develop and prepare students for the future. The application of differentiated learning is expected to accommodate the diversity of students in learning. Differentiated learning is learning that adapts to students' interests, learning preferences, and readiness in order to achieve learning goals. In implementing differentiated learning, there are 3 different aspects, namely, content differentiation, process differentiation, and product differentiation. The aim of this research is to determine the effectiveness of differentiated learning in addressing the diversity of student needs and the impact of implementing differentiated learning. The type of research used is qualitative with a descriptive qualitative research approach. Data collection techniques in this research consisted of observation, interviews and documentation. The data analysis technique in this research consists of data reduction, data presentation and drawing conclusions. The application of differentiated learning in class IV science and science learning at SD N Klangon resulted in the application of differentiated learning being able to address the diversity of students' needs. In implementing learning, students are divided into groups according to their respective learning styles, including audio, visual and kinesthetic. By grouping learning styles, students can optimize task achievement and participate in teaching and learning activities well so that learning goals can be achieved.